Tuturan dalam Novel Rahasia Keluarga Karya Okky Madasari dan Alumni OM Institue - Zahidah, Athiya; Ekowati, Sri Harini; Tajuddin, Shafruddin (Program Studi Pendidikan Bahasa Prancis FBS UNJ, 2024)
In the 21st century, technology is getting more sophisticated. Humans get information quickly and directly. Communication can be done directly or indirectly. The language of communication can be either spoken or written. Writing can be recorded as history. Literary works in the form of novels are in great demand by all circles. This study discusses the story in the family secret novel by Okky Madasari. Writer Okky Madasari is very happy when someone examines his novel. The novel tells about family conflicts in the form of short stories. This study describes the types of speech acts contained in the family secret novel by Okky Madasari and OM Institute Alumni. The method used in this research is descriptive method. A method that analyzes data based on the material obtained without reducing or exceeding the data. The form of research used in this study is a qualitative approach and focuses on content analysis. The speech acts contained in the family secret novel are illocutionary speech acts. There are three intents contained in representative illocutionary, namely stating, informing and refusing. The representative illocutionary speech act states as many as 40 direct speeches, the representative illocutionary speech act informs as many as 10 direct speeches and the representative illocutionary speech act rejects as many as 10 direct speeches.